Urban Heritage Conservation for Sustainable Development: A Case of Kapurthala - Sehgal V.; Kaur H. (My University, 2025)
A princely state before Independence and currently one of the prime examples of administrative and civic neglect for its heritage; Kapurthala has been a witness to its past glory and present obscurity. The city still takes pride in showcasing its unique architectural style in heritage monuments like Jagatjit Palace, Jagatjit Club, Moorish Mosque, but at the same time, it attracts lot of criticism for failure to conserve buildings like Kamra Palace, Nihal Palace (Jallowkhana), Bhoot Bangla. This paper is a critical study of current conditions of the city that includes heritage, physical and social infrastructure. On the basis of observation, photography, reconnaissance and public opinion surveys, to protect the legacy of the city that lies in its rich cultural heritage and to promote the tourism, urban renewal through design proposals and urban design guidelines and strategies were recommended. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2021.